The Influence of Cash Ratio, Net Profit Margin, and Company Size on Dividend Policy - Dea Anggraini; Utami, Ranti; Afriyadi; Novica Indriaty; Tommy Munaf (Future Science, 2024)
The purpose of this study was to determine the effect of cash ratio, net profit margin and company size on dividend policy in consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2018-2022. The research method used in this research is quantitative. The population in this study were 58 main board consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2018-2022. The sampling technique used in this study was purposive sampling. So that the sample obtained was 21 consumer non-cyclicals companies listed on the IDX for the 2018-2022 period. The results showed that partially cash ratio and net profit margin had no effect on dividend policy. Meanwhile, company size partially has a significant effect on dividend policy. It can be concluded that cash ratio, net profit margin and company size have an effect on dividend policy. And the Adjusted R-Squared value is 0.736174, which means that the dividend policy is influenced by the Cash Ratio, Net Profit Margin and Company Size by 73.62% and 26.38% is influenced by other variables not examined in this study.